Nationalism as a logic of partition: theoretical dimensions of Edward Said’s activism on the Palestinian issue - Carvalho, Bruno Sciberras de (Tempo Social, 2020)
Based on the analysis of Edward Said’s works, interviews and political views on Israeli-Palestinian relations, the article discusses how inflections in the author’s activism articulate with the evolution of his theoretical reflections. It is argued that Said’s changes of position on the conflicts of the Palestinian question reflect continuous movements of his theoretical production, particularly the development of critical theses about forms and practices of identity filiation. Although Said changes some opinions over the years, it is pointed out that his theoretical critique of identity logic, especially what he calls the “partition model” of nationalism, as well as the praise of a universalist position, have always been present in his work.